Structural and functional MRI study of the brain, cognition and mood in long-term adequately treated Hashimoto's thyroiditis. - Quinque, E. M.; Karger, S.; Arelin, K.; Schroeter, M. L.; Kratzsch, J.; Villringer, A. (Psychoneuroendocrinology, 2014)
The current study investigated neuropsychological and underlying structural and functional brain alterations in long-term adequately treated patients with Hashimoto's thyroiditis in order to examine much discussed residual complaints in patients in relation to possible long-term neural alterations with a specific interest in the underlying autoimmune process. Eighteen patients with treated hypothyroidism due to Hashimoto's thyroiditis (mean age 32, range 18-54 years; two males; mean treatment duration 4.4 years) and 18 healthy matched control subjects underwent 3-Tesla magnetic resonance imaging (MRI). Voxel-based morphometry was used to investigate grey matter density, resting-state functional MRI to analyse the brain connectivity of areas known to be altered in hypothyroidism and event-related functional MRI to examine brain activity during associative memory encoding. Neuropsychological assessment included memory, working memory, psychomotor speed and attention. We previously reported subclinically reduced mood in this study population and investigated its neural correlates here. Thyroid stimulating hormone, free triiodthyronine, free thyroxine and thyroid peroxidase antibodies were measured in serum. We did not find cognitive deficits or alterations in grey matter density, functional connectivity or associative memory-related brain activity in comparison to the control group and cognition was unrelated to thyroid serum measures in the patient group. Thyroid peroxidase antibodies in the patient group correlated with increased grey matter density in right amygdala and enhanced connectivity between subcallosal and parahippocampal areas. Treatment duration was associated with brain structure in frontal and occipital cortex and connectivity between left amygdala and frontal cortex. Mood correlated with brain areas associated with distinct functional networks, but not with those most prominently affected in depression. In conclusion, no cognitive or neural alterations were detected in this young and otherwise healthy cohort of patients in comparison to a healthy control group and current mood status could not be related to depression-related networks. However, autoimmune activity and treatment duration showed a relationship with depression and hypothyroidism-related brain structure and function. They are thus promising factors to further investigate residual complaints despite biochemically adequate treatment in patients with Hashimoto's thyroiditis. Given the small sample size, all findings require replication.
Keywords: Adolescent; Adult; Affect/*physiology; Brain/*pathology/*physiopathology; Cognition/*physiology; Female; Hashimoto Disease/drug therapy/*pathology/*physiopathology/psychology; Humans; Magnetic Resonance Imaging/*methods; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Thyroxine/therapeutic use; Young Adult